Destinations : - Bailey, Richard E. (McGraw-Hill, 2004)
This process-oriented, paragraph-to-essay level workbook teaches students to write well by drawing on the ways in which they already use language effectively - in thinking, speaking, writing informally, and reading. The text's integrated approach to grammar and its emphasis on writing's real-life applications set it apart from its competitors.